KOMPETENSI PEMBELAJARAN PRAKTIKUM MAHASISWA PENDIDIKAN VOKASIONAL PERTANIAN PADA PEMANFAATAN POTENSI LOKAL - . Suryawati (Partner, 2018)
We studied students competence improvement in managing marginal land by comparing Inquiry Training Agriculture Vocational Education (ITPVP) versus direct instruction (PL) base approach on palmyra palm fruit fibers compost use to remediate shallow and rocky dryland. The study wasdesigned according to true experimental design. We devided students of  Politani into two groups, namely whether they participated on ITPVP or PL base learning. The two groups have homogenious academic prestation indexes. We conducted tests at the end of every  practical. We found, ITPVP group students had significantly (p<0.05)  higher cognitive, affective and phsycomotoric competence, compared to the PL group.  The ITPVP group also had better  agronomic  skills. We conclude the ITPVP base practical for vocational agriculture students improves learning competence, better than the PL approach.